(untitled) - Pater, Walter (Cleveland, 1961)
Oscar Wilde called this collection of essays the "holy writ of beauty." Published to great acclaim in 1837, it examines the work of Renaissance artists such as Winckelmann and the then neglected Botticelli, and includes a celebrated discussion of the Mona Lisa in a study of Da Vinci. The book strongly influenced art students and aesthetes of the day and is still valuable for the insights it offers and the beauty of the writing.
Keywords: English literature